Using adaptive filter as a notch filter to cancel adjacent channel interference in cellular systems: استخدام المرشّح المتكيّف كمرشّح شقوق لإلغاء تداخل القناة المجاورة في الأنظمة الخلويّة - Farah Tawfek Jneikeh, Yaser Emleh, Haitham Alradwan (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
Since the interference/noise signal characteristics such as amplitude, frequency and phase are variable over time and sometimes unknown, therefore, most wireless systems, especially cellular systems, have difficulty extracting the useful signal and its frequency from the distorted signal. So, an adaptive filter is used for this purpose, where its transmission function is adjusted according to an optimization algorithm and this enables it to adapt along with the change in the signal characteristics in order to reach the ideal filter coefficients that permit to reduce the error to the minimum. However, adaptive filter algorithms have evolved to allow the adaptive filter to function as a notch filter by tracking the unknown frequency of the interference signal from adjacent channels in an environment where there is no full knowledge of the signal characteristics. Thus, these algorithms initially estimate the sinusoidal frequency of the interference signal quickly and accurately and then update the filter coefficients using this estimation, and this contributes to remove the noise and the single/multiple narrowband interference from the broadband signal where the frequency response of the adaptive notch filter has sharp rejection characteristics at the notch frequency corresponding to the interference frequency to be removed.